Determination of the cause of mortality in a giant freshwater prawn Macrobrachium rosenbergii nursery in Costa Rica: case analysis - Varela Mejías, Alexander (2018)
This paper presents the findings obtained from a series of analyzes carried out for a freshwater prawn maturation of Macrobrachium rosenbergii in Costa Rica. A large larval production centre had recurrent abortions of gravid females, as well as high mortality in larval and post-larval stages. The results indicate that increases in the presence of organic matter in the water of the tanks caused high prevalence of ectoparasites in the ovigerous masses, as well as high bacterial counts in the water column. This condition generated bacterial and parasitic infections in larvae with severe reduction in production.